Predicting lung adenocarcinoma invasiveness by measurement of pure ground-glass nodule roundness by using multiplanar reformation: a retrospective analysis. Issue 1 (January 2022) - Wang, Q.; Ba, W.; Yin, K.; Shen, J.; Jiang, G.; Liang, Y.; Zhu, Z.; Wu, J.
Abstract : AIM: To explore the value of roundness measurement based on thin-section axial, coronal, and sagittal section computed tomography (CT) images for predicting pure ground-glass nodule (pGGN) invasiveness. MATERIALS AND METHODS: A total of 168 pGGNs in 155 patients (44 male, 111 females; mean age, 55.74 ± 10.57 years), and confirmed by surgery and histopathology, were analysed retrospectively and divided into pre-invasive ( n= 72) and invasive ( n= 96) groups. Photoshop (CS6) software was used to measure pGGN roundness based on conventional axial section, as well as coronal and sagittal sections generated by multiplanar reformation, from thin-section (1-mm-thick) CT lung images. RESULTS: pGGN roundness values, measured in axial, coronal, and sagittal thin-section CT sections from the pre-invasive group were 0.8 ± 0.049, 0.816 ± 0.05, and 0.818 ± 0.043, respectively, while those in the invasive group were 0.745 ± 0.077, 0.684 ± 0.106, and 0.678 ± 0.106; differences between the two groups were significant (all p< 0.001). Binary logistic regression analysis showed that roundness values based on coronal and sagittal sections ( p< 0.001) were better than those from axial sections ( p> 0.05) in predicting pGGN invasiveness, with odds ratio (OR) values of 14.858 and 23.315, respectively. ROC analysis showed that evaluation of roundness measured in sagittal sections was better at predicting pGGN invasiveness than when coronal sections were used (AUC 0.870 versus 0.832). CONCLUSION: Roundness is useful for predicting pGGN invasiveness, with measurements from coronal and sagittal sections better than those from conventional axial sections, with sagittal section images having the best predictive value. Highlights: Roundness is an objective quantitative indicator to predict pGGN invasiveness. Coronal and sagittal MPR roundness have a better predictive value. Multiplanar measurement of pGGN roundness can help the clinical management.